Publication Pattern in Oryza (Oryza sativa L.) from 1986-1995: A Bibliometric Study - Ramesh, L. S. R. C. V.; Venkata Ramana, P.; Vali Hussain, Mohd. (Journal of Information and Knowledge, 2000)
Analyses the papers published in the quarterly International Rice Journal ’Oryza’ from 1986-1995. Attempts to analyse the yearwise distribution of papers, the authorship pattern, yearwise distribution of degree of collaboration, the geographical location of contributors, discipline/subject wise distribution of papers, the types of affiliation, average length of articles and study of references. Author affiliations emphasizes the dominance of Indian authors and the multiple authorship belonging to academic institutions. Suggests increase in volume of papers, received articles to cover the latest research developments in agricultural field around the globe.